Expert evidence / Abdul Rauf A. Rahman - A. Rahman, Abdul Rauf (Faculty of Law, 1985)
In the modern world of today, disputes brought to the courts for settlement have been increasingly becoming more complex and technical. Expeztise in the law does not fully equip judges to solve the disputes as the disputes cover a wide range of interests and expertise. Thus there is an increasing need for the assistance of experts to assist the court by their knowledge, skill and experience in their respective trade or professions. However, their assistance cannot be taken blindly as their function are only to assist and not to take over the decision-making function of the court. Furthermore experts not only assist the courts but they also have vested interests with the parties which called them. It is on this background that this paper is written to highlight the principles guiding the use of expert evidence in courts with a special reference made to the Malaysian legal position.